A Remote Nutritional Intervention to Change the Dietary Habits of Patients Undergoing Ablation of Atrial Fibrillation: Randomized Controlled Trial - Goni, Leticia; de la O, Víctor; Barrio-López, M Teresa; Ramos, Pablo; Tercedor, Luis; Ibañez-Criado, Jose Luis; Castellanos, Eduardo; Ibañez Criado, Alicia; Macias Ruiz, Rosa; García-Bolao, Ignacio; Almendral, Jesus; Martínez-González, Miguel Ángel; et al. (JMIR Publications, 2020)
BackgroundThe Prevention With Mediterranean Diet (PREDIMED) trial supported the effectiveness of a nutritional intervention conducted by a dietitian to prevent cardiovascular disease. However, the effect of a remote intervention to follow the Mediterranean diet has been less explored. ObjectiveThis study aims to assess the effectiveness of a remotely provided Mediterranean diet-based nutritional intervention in obtaining favorable dietary changes in the context of a secondary prevention trial of atrial fibrillation (AF). MethodsThe PREvention of recurrent arrhythmias with Mediterranean diet (PREDIMAR) study is a 2-year multicenter, randomized, controlled, single-blinded trial to assess the effect of the Mediterranean diet enriched with extra virgin olive oil (EVOO) on the prevention of atrial tachyarrhythmia recurrence after catheter ablation. Participants in sinus rhythm after ablation were randomly assigned to an intervention group (Mediterranean diet enriched with EVOO) or a control group (usual clinical care). The remote nutritional intervention included phone contacts (1 per 3 months) and web-based interventions with provision of dietary recommendations, and participants had access to a web page, a mobile app, and printed resources. The information is divided into 6 areas: Recommended foods, Menus, News and Online resources, Practical tips, Mediterranean diet classroom, and Your personal experience. At baseline and at 1-year and 2-year follow-up, the 14-item Mediterranean Diet Adherence Screener (MEDAS) questionnaire and a semiquantitative food frequency questionnaire were collected by a dietitian by phone. ResultsA total of 720 subjects were randomized (365 to the intervention group, 355 to the control group). Up to September 2020, 560 subjects completed the first year (560/574, retention rate 95.6%) and 304 completed the second year (304/322, retention rate 94.4%) of the intervention. After 24 months of follow-up, increased adherence to the Mediterranean diet was observed in both groups, but the improvement was significantly higher in the intervention group than in the control group (net between-group difference: 1.8 points in the MEDAS questionnaire (95% CI 1.4-2.2; P<.001). Compared with the control group, the Mediterranean diet intervention group showed a significant increase in the consumption of fruits (P<.001), olive oil (P<.001), whole grain cereals (P=.002), pulses (P<.001), nuts (P<.001), white fish (P<.001), fatty fish (P<.001), and white meat (P=.007), and a significant reduction in refined cereals (P<.001), red and processed meat (P<.001), and sweets (P<.001) at 2 years of intervention. In terms of nutrients, the intervention group significantly increased their intake of omega-3 (P<.001) and fiber (P<.001), and they decreased their intake of carbohydrates (P=.02) and saturated fatty acids (P<.001) compared with the control group. ConclusionsThe remote nutritional intervention using a website and phone calls seems to be effective in increasing adherence to the Mediterranean diet pattern among AF patients treated with catheter ablation. Trial RegistrationClinicalTrials.gov NCT03053843; https://www.clinicaltrials.gov/ct2/show/NCT03053843